Frequency of Urinary Tract Infection in Febrile Children without Any Focus on Infection - Atiya Jogezai, Varda Tuz Zahra, Ambreen Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In newborns and young children, a urinary tract infection is a frequent hidden cause of fever. Children younger than a year old who appear with fever and symptoms of UTI are usually given treatment for something else. Objectives: The objective of this study was to assess the prevalence of UTI in children presenting to a tertiary care hospital between the ages of 1 month and 36 months with nonspecific fever. Duration and study settings: The Children’s Hospital Pakistan Institute of Medical Science, SZABMU, Islamabad, was the site of this trial, which ran from Jan 2018 to June 2018. Study design: Descriptive cross sectional Methodology: After a complete medical history and physical examination, a urine sample was taken for testing and culture using a soft tube in younger children and a clean catch approach in older children or those who are cooperative. Urisys 2400 was used to analyse the urine samples. Larger children’s urine samples were grown on CLED agar plates (cysteine lactose, electrolyte deficient). Clinitek Siemens, a haematology analyser, was used to determine the number of white blood cells in the blood. The Pakistan Institute of Medical Sciences in Islamabad is home to a state-of-the-art laboratory where tests including leucocyte count, urine DR, and culture were conducted. A pre-designed proforma was used to record the patient’s demographic information, medical history, diagnosis, and laboratory results. Results: In this study, 6.47 percent (n=18) of 278 children aged 1 to 36 who presented to a tertiary care hospital with a fever and no other obvious signs of infection were found to have a urinary tract infection. Conclusion: Children arriving to a tertiary care hospital with a fever and no other signs of infection are not likely to have a urinary tract infection. Keywords: UTI in children with diffuse fever and no obvious source of infection.